Impact of Critical Care Transesophageal Echocardiography in Medical–Surgical ICU Patients: Characteristics and Results From 274 Consecutive Examinations. (September 2020) - Arntfield, Robert; Lau, Vincent; Landry, Yves; Priestap, Fran; Ball, Ian
Objective: Critical care echocardiography has become an integral tool in the assessment and management of critically ill patients. Critical care transesophageal echocardiography (TEE) offers diagnostic reliability, superior image quality, and an expanded diagnostic scope to transthoracic echocardiography. Despite its favorable attributes, TEE use in North American intensive care units (ICUs) remains relatively undescribed. In this article, we seek to characterize the feasibility, indications, and clinical impact of a critical care TEE program. Design: Retrospective, observational study. Setting: Tertiary care, academic critical care program consisting of 2 hospitals in Ontario, Canada. Participants: Consecutive critical care TEE examinations on ICU patients performed between December 2012 and December 2016 Interventions: None. Measurements and Main Results: Consecutive critical care TEE studies on ICU patients from December 1, 2012, to December 31, 2016, were reviewed. The TEEs performed on cardiac surgery patients and those without reports were excluded. Examination details, including indications, complications, examination complexity (number of views, Doppler techniques), and clinical recommendations were aggregated and analyzed. Two hundred seventy-four TEE studies were performed by 38 operators. Common indications for TEE studies were hemodynamic instability (45.2%), assessment for infective endocarditis (22.2%), and cardiac arrest (20.1%). A change in patient management was proposed following 79.5% of TEE studies. Thirty-eight percent of TEE studies were performed during evening hours or on weekends. There were no mechanical complications. Conclusions: Our observational data support intensivist-performed TEE as being safe and therapeutically influential across a broad range of indications. Our program's demonstrated feasibility and impact may act as a model for TEE adoption in other North American ICUs.